Hybrid direct carbon fuel cell-thermoradiative systems for high-efficiency waste-heat recovery. (15th October 2019) - Zhang, Xin; Du, Jianying; Ang, Yee Sin; Chen, Jincan; Ang, Lay Kee
Graphical abstract: Highlights: A new hybrid device for high-efficiency waste-heat recovery is presented. Device performance is greatly improved compared with subcomponents. System performance is superior to other carbon fuel cell-based hybrid systems. Paving a new route to boost the energy conversion efficiency of carbon fuel cells. Abstract: Medium-grade waste heat released from direct carbon fuel cell contains enormous useful energy, which can be recycled for secondary power generation. However, conventional solid-state devices for harvesting moderate-grade waste heat, such as thermophotovoltaics and thermoelectric converters, are limited by low power generation and conversion efficiency. Here a hybrid system consisting of a direct carbon fuel cell and a Gallium antimonide thermoradiative device is proposed, where the effects of thermal coupling between the subsystems, over-potential losses in the fuel cell, non-radiative recombination and sub-bandgap radiation in the thermoradiative device, and various heat losses within the system are included. The thermoradiative device recycles the waste heat produced in the direct carbon fuel cell to generate additional electricity, thus enabling a significant improvement in power generation. The performance characteristics and the parametric design strategies of the hybrid system are investigated. The simulation results predict a maximum power density of 516 W·m −2 at the fuel cell temperature of 972 K, which exhibits a 1.48 times improvement compared with the standalone direct carbon fuel cell. This work reveals the potential of the direct carbon fuel cell-thermoradiative device hybrid system for waste heat recycling and opens up a new avenue to boost the energy conversion efficiency of carbon fuel cells.